Analisis Pengaruh Informasi Keuangan dan Non Keuangan yang Mempengaruhi Underpricing saat Initial Public Offering (IPO) di Bursa Efek Indonesia pada Tahun 2017-2021 - Devi Trining Tyas; Nur Diana; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
One of the most difficult problems a company faces when offering shares for the first time is determining the amount of the initial offering price. The intentional factor to attract investors in the primary market can cause the underpricing. Underpricing is one of the common phenomena and symptoms that occur during the Initial public offering (IPO) process. This study aims to determine the effect of financial and non-financial information on underpricing when conducting an IPO on the Indonesia Stock Exchange in 2017-2021. The variables used in this study are percentage of stock offerings, return on equity, underwriter, price earning ratio, company age, current ratio, and auditor reputation.The type of research used in conducting this research is correlational research. The sampling method in this research is using purposive sampling method which obtained as many as 148 samples of companies that conduct IPOs on the Indonesia Stock Exchange. The data analysis technique used in this research is multiple regression analysis.The results showed that the price earning ratio and the percentage of stock offerings had a positive and significant effect on underpricing and auditor reputation had a negative and significant effect on underpricing. Meanwhile, the return on equity variables, current ratio, underwriter, and company age have no effect on underpricing of companies conducting IPOs in 2017-2021.Keywords: Initial public offering, Underpricing, Price earning ratio, Return on equity, Current ratio, Underwriter, Share Offering Percentage, Company Age, Auditor Reputation.